2013
DOI: 10.1103/physrevb.88.014112
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic charge-transfer transition in Bi1xLaxNiO3

Abstract: The nature of triclinic to orthorhombic phase transition, at which colossal negative thermal expansion is observed, and the magnetic ordering of Bi 1−x La x NiO 3 have been investigated with neutron powder diffraction (NPD) and x-ray absorption spectroscopy techniques. The presence of a charge-transfer transition from (Bi/La) 3+ 0.5 Bi 5+ 0.5 Ni 2+ O 3 to (Bi/La) 3+ Ni 3+ O 3 , accompanied by the simultaneous structural distortion, was confirmed. The NPD data also revealed that magnetic ordering is present onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The strain ΔL / L (400 K) increases with increasing temperature up to 270 K indicating the normal positive thermal expansion, but decreases above 270 K. The average observed α L between 270 and 400 K is −49 × 10 −6 K −1 and the maximum negative slope between 320 and 380 K corresponds to a linear thermal expansion coefficient of −82 × 10 −6 K −1 [24]. It was confirmed that the oxidation of Ni ion from 2+ to 3+ was the origin of this volume shrinkage by XAS measurement [32]. …”
Section: Nte In A- or B- Site Substituted Perovskite Compound Binio3mentioning
confidence: 86%
“…The strain ΔL / L (400 K) increases with increasing temperature up to 270 K indicating the normal positive thermal expansion, but decreases above 270 K. The average observed α L between 270 and 400 K is −49 × 10 −6 K −1 and the maximum negative slope between 320 and 380 K corresponds to a linear thermal expansion coefficient of −82 × 10 −6 K −1 [24]. It was confirmed that the oxidation of Ni ion from 2+ to 3+ was the origin of this volume shrinkage by XAS measurement [32]. …”
Section: Nte In A- or B- Site Substituted Perovskite Compound Binio3mentioning
confidence: 86%
“…18,19 Recently, we reported that Bi 0.95 La 0.05 NiO 3 shows a large NTE with a L ¼ À82 ppm/K in the temperature range of 320-380 K, owing to a temperature induced intermetallic charge transfer transition. [20][21][22] The parent compound, BiNiO 3 , has a unique valence state of Bi 3þ 0.5 Bi 5þ 0.5 Ni 2þ O 3 and a triclinic structure, where Bi 3þ and Bi 5þ occupy distinct crystallographic sites. [23][24][25] Substitution of La for Bi stabilizes the valence state of (Bi/La) 3þ Ni 3þ O 3 and leads to temperature-induced melting of charge disproportionation accompanied with simultaneous charge transfer between Bi 5þ and Ni 2þ ions.…”
mentioning
confidence: 99%
“…[20][21][22] The XRD patterns were collected at various temperatures with a D8 ADVANCE diffractometer (Bruker) with Cu Ka radiation. The lattice parameters and fractions of low-temperature triclinic and high-temperature orthorhombic phases were refined by conducting a Rietveld analysis using TOPAS software.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the first class of NTE phenomena have revealed contentious issues regarding the interplay of magnetism, disorder, charge disproportionation, and their volume coupling and continue to intrigue physicists [2][3][4][5][6][7][8]. The second class of behavior, which we term structural NTE (SNTE), is observed in both metallic and insulating materials without competing order [9][10][11][12][13][14].…”
mentioning
confidence: 99%